Anaerobic treatment of real cosmetic wastewater in a lab-scale UASB using fungal biocatalysts: COD/TOC removal and methane yield (Pleurotus ostreatus vs Trametes versicolor) - Durmus, Barbaros; Kocer, Nilufer Nacar; Senel, Gulsad Uslu (Elsevier Sci Ltd, 2026)
Real cosmetic wastewater is chemically complex and often difficult to treat using conventional processes. This study investigated continuous anaerobic treatment in a 3.0-L upflow anaerobic sludge blanket (UASB) reactor operated with polyurethane-immobilized white-rot fungi, Pleurotus ostreatus and Trametes versicolor. Real plant effluent was fed under hydraulic retention times (HRT) of 15, 30, and 45 h to evaluate pollutant removal and biogas performance. The reactor remained stable throughout operation, with effluent pH between 6.4 and 6.7 and intact fungal pellets. COD removal increased with HRT, reaching 84.0 % for P. ostreatus and 90.4 % for T. versicolor at 45 h. TOC removal followed a similar trend, attaining 78.0 % and 76.0 %, respectively. Color removal reached 68.7 % for P. ostreatus and 79.5 % for T. versicolor. Cumulative biogas production was 300 mL for P. ostreatus and 250 mL for T. versicolor, with methane fractions of 60 % and 55 %. Specific methane yields increased with HRT, achieving 178 and 165 mL CH4 g(-1) VS at 45 h. Overall, T. versicolor exhibited superior decolorization, whereas P. ostreatus produced more methane-rich biogas. These findings demonstrate the potential of fungal UASB systems as low-energy, biologically driven treatment options for dye-rich cosmetic wastewater.
Keywords: Cosmetic industry wastewater; Anaerobic biodegradation; Upflow Anaerobic Sludge Blanket (UASB) reactor; Pleurotus ostreatus; Trametes versicolor; Chemical Oxygen Demand (COD)